HUBUNGAN AKTIVITAS FISIK DAN WAKTU DI DEPAN LAYAR ELEKTRONIK DENGAN INDEKS MASSA TUBUH SISWA SD ISLAM HIDAYATULLAH SEMARANG - Andika Rikarno Putra; Dina Rahayuning Pangestuti; Martha Irene Kartasurya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
In Indonesia, 18.8% of the children are either overweight or obese. A child will stay overweight until adulthood unless changes in lifestyle are made. Sedentary behaviour such as moderate – vigorous intensity physical activity less than 2 hours a day and screen time more than 2 hours a day may cause childhood obesity. The goal of this research is to analyze the correlation between physical activity and screen time with BMI in primary school students. This is a quantitative analytical research using cross sectional design study. The population are136 5 th grade students. Slovins formula is used to count the sample of this research. 35 students are used to test the validity of the questionnaire while the rest (101 students) are used as sample. Data is taken using 3 Day Physical Activity Recall and Food Recall questionnaire. Bivariate Analysis is done using Person – Product Moment and Rank Spearman. The result shows that 52% of the students are overweight or obese, 54% of the students spend less than 1 hour doing physical activity each day and 79% of the students has more than 2 hours of screen time a day. Physical activity (p=<0.001, r=0.741) and screen time (p=0.045, r=0.209) correlates with the students Body Mass Index. Energy intake (p=0.128, r=-0.174), carbohydrate intake (p=0.064, r=-0.211), fat intake (p=0.452, r=-0.086), mother's BMI (p=0.248, r=0.176) and father's BMI (p=0.218, r=0.187) doesn't correlate with the students BMI. Screen time and physical activity related with the students BMI.